Low agreement between the fitnessgram criterion references for adolescents - Diogo Henrique Constantino Coledam; João Pedro Batista Júnior; Maria Fátima Glaner (Sociedade de Pediatria de São Paulo, 2015)
OBJECTIVE: To analyze the association and agreement of fitnessgram reference criteria (RC) for cardiorespiratory fitness, body mass index (BMI) and strength in youth. METHODS: The study included 781 youth, 386 females, aged 10 to 18 years of Londrina-PR. It were performed cardiorespiratory fitness and muscular strength tests and was calculated body mass index. The association between the tests was analyzed using Poisson regression to obtain prevalence ratio (PR) and confidence intervals of 95%, while agreement of the reference criteria was tested by Kappa index. RESULTS: Significant associations were found between cardiorespiratory fitness and BMI (PR=1,49, 1,27-1,75), muscle strength and BMI (PR=1,55, 1,17-2,08), cardiorespiratory fitness and muscle strength (PR=1,81, 1,47-2,24). The agreement between reference criteria ranged from weak to fair, 48.8% (k=0.05, p=0.10) for cardiorespiratory fitness and BMI, 52.9% (k=0.09, p=0.001) for muscle strength and BMI and 38.4% (k=0.22, p<0.001) for cardiorespiratory fitness and muscle strength. CONCLUSIONS: Although RC for cardiorespiratory fitness, muscle strength and BMI are associated, the agreement between them ranged from weak to fair. To evaluate health related physical fitness it is suggest the execution of all tests, since each test has specific characteristics.